A Semantic Analysis of Grammatical Meaning in Bernadya’s Album Sialnya, Hidup Harus Tetap Berjalan - Lestari, Tri; Zain, Nurdiana; Fatmala, Siti; Firmansyah, Dody (Universitas Nusantara PGRI Kediri, 2025)
Semantics has various types of meanings contained within it, one of which is grammatical meaning. Grammatical meaning is a meaning that arises due to the processes of affixation (addition of affixes), reduplication (repetition), and composition (compounding). Grammatical meaning in this study is used to analyze the lyrics of songs on Bernadya's latest album titled